2018
DOI: 10.1108/el-03-2017-0062
|View full text |Cite
|
Sign up to set email alerts
|

An infodemiology study on breast cancer in Iran

Abstract: Purpose According to the studies conducted in Iran, the breast cancer is the most frequent type of cancer among women. This study aimed to explore the state of health information supply and demand on breast cancer among Iranian medical researchers and Iranian Web users from 2011 to 2015. Design/methodology/approach A mixed method research is conducted in this study. In qualitative part, a focus group interview is applied to the users to identify their selected keywords searched for breast cancer in Google. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Therefore, health campaigns should use these platforms to reach a wider audience. Regarding the content of websites, it is interesting to analyze the way the internet offers its users the specific content [8,9,28]. Websites can shape ideas about inclusion and disseminate rigorous information or, on the contrary, lack basic content about the diagnosis and its intervention mechanisms [29,30] from searches and information (based on supply and demand, as we will see in the following section).…”
Section: Visibility and Normalization: Towards Social Inclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, health campaigns should use these platforms to reach a wider audience. Regarding the content of websites, it is interesting to analyze the way the internet offers its users the specific content [8,9,28]. Websites can shape ideas about inclusion and disseminate rigorous information or, on the contrary, lack basic content about the diagnosis and its intervention mechanisms [29,30] from searches and information (based on supply and demand, as we will see in the following section).…”
Section: Visibility and Normalization: Towards Social Inclusionmentioning
confidence: 99%
“…The analysis of searches has become a useful method to understand and explain human behavior [31] and discover the population's level of awareness about different conditions such as autism [32]. Understanding search trends and search behavior, as well as the frequency and location of searches in time and space, can be effective for developing public health policies [25,28,33].…”
Section: Infodemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…The search term generation can be carried out in various ways. The study in [37] collects search terms from interviewing respondents who had been stricken with the disease and from consultation with a pathologist. A search term can also be generated from grouping several variables related to the object of research [29] and from related queries found in GT [15] [38].…”
Section: Search Term Categorization and Generationmentioning
confidence: 99%